Avaliação da atividade imunomoduladora de nanopartículas de prata em células humanas do sangue periférico - Dutra, Dasaiev Monteiro (2015)
Introduction: Is spite of the promising studies in immunotherapy and the fabrication of dental materials with antimicrobial activity, there are few studies in the literature evaluating the immunomodulatory action of silver nanoparticles (AgNP) in human cells from the whole blood. Objective: The aim of this study was to evaluate the immodulatory activity of silver nanoparticles in human peripheral blood cells. Material and Methods: Silver nanoparticles were synthesized following the Turkevich method at final concentration of 3.72 µg/ml. Nanoscale particles with rounded shape were observed by Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) of the solution stabilized by carboxymethylcellulose ten days after the synthesis. Peripheral blood was collected from six healthy volunteers in containing tubes. Samples were diluted in RPMI1640 medium and incubated for 24h/37ºC/5% CO2 in the presence 5 µg/ml phytohaemagglutinin (PHA), 1 µg/ml lipopolysaccharide (LPS) and AgNP. Cytokine titration (TNFa, IL1ß, IFN?, IL6, IL10, IL-4) was performed by ELISA. Nitric oxide (NO) was measured by Griess reaction. Results: Increased production of IL-6 (p=0.0037) e NO (p=0.022) was observed after AgNP stimulation. The induction of IFN?, TNF-a, IL1ß, IL-4 by AgNP was similar to basal levels. Interestingly, only the IL-6 response correlated positively with IL-4 production (p=0.033, r=0.845). Conclusion: Results suggest that L-6 is preferentially induced by AgNP in human peripheral blood cells.